Investigations on the Microstructure, Microsegregation and Hardness Properties of Bead on Plasma Arc Welded C-276 Alloy. (2018) - Subramani, P.; Shetty, Sanket; Anirudhapandit, R.; Hari, P.R.; Gokul Kumar, K.; Manikandan, M.; Arivazhagan, N.; Siva Shanmugam, N.
Abstract: The present study investigates the microstructure, microsegregation, and microhardness of alloy C-276 plates by a bead on trials of plasma arc welding (PAW). The bead – on welds were carried out by autogenous plasma welding using melt in mode technique. Microstructural characterization studies were performed using optical and scanning electron microscopy (SEM) techniques. The studies showed the presence of close networks of fine equiaxed dendrite structures while employing lower heat inputs. Whereas the increasing heat energy input demonstrates the occurrence of columnar dendrite structures. SEM/EDAX analysis demonstrates the presence of secondary phases of P and µ in the fusion zone. Energy Dispersive X-Ray Analysis (EDAX) analysis was performed to infer the microsegregation of alloying elements. Microhardness study was carried out to evaluate the hardness of the weld zones in different heat input. The hardness test revealed that on increasing the heat input, the hardness values were impoverished.